Spectrofluorometric method for sensing cobalt (II) ion in environmental sample using Ru(dcpy)2(SCN)2 receptor - Hawra Abdulmajeed; Esam Bakir (Results in Chemistry)
Fluorometric assay was employed for the detection of Co2+ ions based on their rapid reaction with Ru(dcpy)2(SCN)2 as the receptor in acetate buffer solution (pH = 3.50). A high fluorescence intensity of the receptor was observed in an acetate buffer at pH = 3.50. The calibration curve was plotted between the fluorescence emission of the receptor at λ = 633 nm versus the Co2+ concentration. The detection (LOD) and quantitation (LOQ) limits were determined to be 04.95 and 14.97 µM (R2 = 0.99), respectively. The selectivity of suggested method was obtained for Co2+ outweighs that of transition metal cations with 2 % significant interference with Ni2+. The recovery of the Co(II) ions founded 99.6 %. The experiments and electronic surface mapping(ESP) were illustrated the chemical reactivity of receptor and Co(II). The Co(II) was attached to CO rather than −NCS group of the receptor. The proposed method was successes in the determination of Co(II) in the environmental water sample.